The Role of Trust in Student Perceptions of University Sexual Assault Policies and Services - Marques, Olga; Couture-Carron, Amanda; Frederick, Tyler; Scott, Hannah (Canadian Journal of Higher Education, 2020)
Many post-secondary institutions are developing policies and programs aimed at improving responses to sexual assault experienced by students. In some areas, such as Ontario, Canada, the government has mandated post-secondary institutions to do so. However significant these initiatives, they are predicated on the assumption that students trust, and want to engage with, the university following sexual violence. This study explores students’ perceptions of sexual assault policies and services on one mid-size university campus focusing specifically on how trust factors into reporting sexual victimization and using services. Findings show that students believe that sexual assault policies and programs exist, but this does not mean students are willing to use such resources or that they even trust that their university has students’ needs and interests at the fore. This paper discusses policy and programmatic considerations for building student trust in their post-secondary institutions to encourage student use of campus support.